2005
DOI: 10.1590/s0034-71672005000400012
|View full text |Cite
|
Sign up to set email alerts
|

A participação da família no cuidado ao prematuro em UTI Neonatal

Abstract: This study aimed at analyzing the family participation in the premature assistance in a university hospital neonatal ICU. Data were collected from the participant observation. Results showed that despite of the mother's presence in the daily life of their premature children placed in a hospital, family isn't inserted in the work process and mothers are the only ones who take part of the cares. This participation basically happens in the execution of maternity care, especially at the medium risk unity, the moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
43

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 1 publication
0
7
0
43
Order By: Relevance
“…This is because the team itself and the institution-with its protocols and routines regarding family presence in the environment -prevent her from exercising her function. It has already been found that the relationship between nurses and mothers can significantly affect how women perceive their experience of motherhood, since the establishment of these interactions may facilitate or restrict their ability to take on the role of mother (12) . Inhibitory actions performed by nurses, either consciously or unconsciously, place them in the role of 'experts', cementing their power over the child by means of care routines, while mothers are relegated to the role of mere spectators of the care provided (12)(13) .…”
Section: Discussionmentioning
confidence: 99%
“…This is because the team itself and the institution-with its protocols and routines regarding family presence in the environment -prevent her from exercising her function. It has already been found that the relationship between nurses and mothers can significantly affect how women perceive their experience of motherhood, since the establishment of these interactions may facilitate or restrict their ability to take on the role of mother (12) . Inhibitory actions performed by nurses, either consciously or unconsciously, place them in the role of 'experts', cementing their power over the child by means of care routines, while mothers are relegated to the role of mere spectators of the care provided (12)(13) .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, maternal exclusion is common, justified by performing invasive procedures, time of medical visits and reduced physical space (17) .…”
Section: Learning Provided At the Circle Of Culturementioning
confidence: 99%
“…The nurse has a fundamental role concerning the involvement of the parents in the activities of the NICU, particularly regarding guidance in the first visit. This professional should provide support in order to reduce the anxiety and fear that the parents of the newborn feel, providing minimum conditions of comfort, trying to respond to concerns and providing information on the health of the newborn, the treatment and the equipment used (4) .…”
Section: Cuidar Del Recién Nacido En La Presencia De Sus Padres: Vivementioning
confidence: 99%
“…Given this premise, in the act of caring for people and through observations of the quotidian in the NICU - Although several studies have addressed the participation of the parents of newborn babies hospitalized in the NICU (4,(7)(8)(9)(10)(11)(12) , the present study is based on the fact that, of the literature investigated, few studies emphasize the themes that seek to comprehend this experience from the perspective of the nurse. Therefore, this study aimed to comprehend how nurses experience the care provided in the NICU faced with the presence of the parents of the newborns.…”
Section: Cuidar Del Recién Nacido En La Presencia De Sus Padres: Vivementioning
confidence: 99%